Analisis Naratif Pada Proses Pembelajaran Bahasa Jepang di Perguruan Tinggi dan Pengaruhnya Terhadap Pilihan Masa Depan Pembelajar Setelah Lulus - Fatmawati Djafri (JLA (Jurnal Lingua Applicata), 2018)
This study examines the significant factors constituted in the meaning-making process of Japanese learning in higher educational context. It employs narrative inquiry approach to investigate the process of motivational change among Japanese learners and how it has impacted on their future choices after graduating from university. Based on the analysis using theoretical frameworks of Dörnyei's L2 Motivational Self System and Norton's investment in language learning, this study found two types of motivational changes experienced by Japanese learners, namely the initial-confirmation/practical-development type and the initial-anxiety-withdrawal type. The result of this study proposes some key roles of Japanese department as a higher educational institution which plays in fostering global human resources and provides important insights into the development of Japanese language education in Indonesia.